1993
DOI: 10.1037/0097-7403.19.2.121
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms responsible for reduced contextual conditioning with massed unsignaled unconditional stimuli.

Abstract: Massed presentation of unsignaled shock results in less conditional freezing to contextual cues than do distributed presentations. Consistent with an account of the learning deficit based on the perceptual-defensive-recuperative theory, the massed-shock deficit was attenuated by preexposure to shock or the conditioning context. This formulation was also successfully applied to the deficit in conditioning that occurs when a single shock is given immediately after placement in a context. Opponent-process theory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
81
1
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(89 citation statements)
references
References 73 publications
6
81
1
1
Order By: Relevance
“…Third, perhaps freezing that occurs while an animal is in the black box during a context preference test results in the animal spending a relatively long time in the former shock context. If this happens, then the inference that the former shock context's excitatory strength is low would be incorrect (see also Fanselow, DeCola, & Young, 1993). With regard to Odling-Smee's finding that signaled-shock rats spent more time in the black box than unsignaled-shock rats, the latter two arguments actually imply that the signaled-shock rats were more fearful than the unsignaled-shock rats.…”
mentioning
confidence: 82%
“…Third, perhaps freezing that occurs while an animal is in the black box during a context preference test results in the animal spending a relatively long time in the former shock context. If this happens, then the inference that the former shock context's excitatory strength is low would be incorrect (see also Fanselow, DeCola, & Young, 1993). With regard to Odling-Smee's finding that signaled-shock rats spent more time in the black box than unsignaled-shock rats, the latter two arguments actually imply that the signaled-shock rats were more fearful than the unsignaled-shock rats.…”
mentioning
confidence: 82%
“…Glutamatergic modifications in excitatory neurotransmission-in particular, NMDAR and AMPAR-within the amygdala participate in different components of fear learning, including acquisition, expression, and extinction (Miserendino et al, 1990;Fanselow and Kim, 1994;Walker and Davis, 2002). Increased excitatory neurotransmission in the BLA could also enhance fear conditioning (Fanselow et al, 1993).…”
Section: Stress-enhanced Fear Expressionmentioning
confidence: 99%
“…By contrast, there were no differences in GluA2 or GluN1 levels in stressed or metyrapone-treated groups. Because facilitating glutamatergic activity at AMPAR enhances the rate of fear conditioning (Kim et al, 1993) and SEFL occurs predominantly by increasing the rate of fear conditioning (Fanselow et al, 1993), the long-term increase in GluA1 subunits is a highly plausible mechanism for the expression of SEFL.…”
Section: Metyrapone Prevents a Post-stressor Glua1 Increasementioning
confidence: 99%
“…A very general excitatory learning rule is that memory is stronger when training trials are "spaced" or distributed in time (Ebbinghaus 1885(Ebbinghaus /1913Carew and Kandel 1973;Fanselow and Tighe 1988;Fanselow et al 1993;Tully et al 1994;Kogan et al 1997;Freudenthal et al 1998;Barela 1999;Josselyn et al 2001). We recently reported that, in contrast to most acquisition learning, more short-and long-term extinction of cue fear followed temporally massed CS presentations than spaced presentations (Cain et al 2003).…”
mentioning
confidence: 99%